Synthesis, DFT calculations, and anti-proliferative evaluation of pyrimidine and selenadiazolopyrimidine derivatives as dual Topoisomerase II and HSP90 inhibitors - Samar El-Kalyoubi; Samiha A. El-Sebaey; A. M. Rashad; Hanan A. AL-Ghulikah; Mostafa M. Ghorab; Sherin M. Elfeky (Taylor & Francis Group, 2023)
Novel series of aminopyrimidines bearing a biologically active cyclohexenone 3a-f and oxo-selaneylidene moiety 4, besides selenadiazolopyrimidines (5a-e and 7), were synthesised using 5,6-diaminouracils as starting materials. Compound 3a exhibited strong anti-proliferative activity against three cell lines: HepG-2 (IC50 14.31 ± 0.83 µM), A-549 (IC50 30.74 ± 0.76 µM), and MCF-7 (IC50 27.14 ± 1.91 µM). Also, it was four times more selectively cytotoxic against WI-38 cell lines than doxorubicin. Furthermore, Topoisomerase II (IC50 4.48 ± 0.65 µM) and HSP90 (IC50 1.78 ± 0.11 µM) were both strongly inhibited in vitro by 3a. The cell cycle was halted at the G1-S phase, and total apoptotic cells were 65 times more than control Hep-G2 cells. Besides, it increased caspase-3 gene expression, triggering mitochondrial cell death. Molecular docking study indicated that it could bind to Topoisomerase II and HSP90 binding sites in an inhibitory mode. Its geometric properties were investigated using the density functional theory (DFT). Furthermore, compound 3a demonstrated in silico good oral bioavailability.